Socio-spatial analysis of residential water demand in Mexico City - Ramos-Bueno, Arturo; Perevochtchikova, Maria; Chang, Heejun (Tecnología y ciencias del agua, 2021)
Water management in cities has turned increasingly challenging, as urban water demand escalation takes place in a context of reduction of available freshwater sources. These concerns have evidenced the need to integrate water supply, drainage, and sanitation from the Integrated Urban Water Management (IUWM) paradigm. To study water supply component, it is important to consider the analysis of urban water demand determinants. In the case of Mexico City there is a lack of an accurate diagnosis for these determinants despite the fact it faces multiple water problems. Therefore, the present study aims to estimate residential water demand and its determinants in Mexico City at a neighborhood scale for the year 2010, based on official measured data. Analyzed determinants are related to socioeconomic, urban density and access to water services issues; by employing the models of Ordinary Least Squares multiple regression (providing global and spatially stationary results) and the Geographically Weighted Regression (presenting spatially varying coefficients). Results point to the central area of the city as priority to implement strategies from the IUWM. The estimation provides a deeper comprehension of water crisis in Mexico City from a water demand-side view, it is also useful for decision-making.